Tasks, Technology, and Factor Prices in the Neoclassical Production Sector - Andreas Irmen (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper introduces tasks into the neoclassical production sector. Competitive firms choose the profit-maximizing amounts of factor-specific tasks that determine their factor demands and output supplies. We show that the effect of factor-augmenting technical change on relative and absolute factor prices can be decomposed into a productivity effect and a task-demand effect of opposite sign. These effects appear since the novel task-based approach distinguishes between the demands for tasks and the demands for factors. This perspective provides a new intuition for the emergence of relative and absolute factor biases and the role of the elasticity of substitution.
Keywords: O33; O41; 330; technical change; factor prices; factor-specific tasks; neoclassical production